Urinary hepcidin level as an early predictor of iron deficiency in children: A case control study - Gharib Amal F; Sanad Mohammed (BMC, 2011)
Abstract Background The ideal screening test would be capable of identifying iron deficiency in the absence of anemia. We tried to detect role of urinary hepcidin-25 level in early prediction of iron deficiency in children. Methods This is a case control study performed on 100 children in Hematology Unit of Pediatric Department, Zagazig University Hospital, Egypt. Our study included 25 cases of iron deficiency (ID) stage-1 (iron depletion), 25 cases ID stage-2 (iron-deficient erythropoiesis), 25 cases ID stage-3 (iron deficiency anemia) and 25 healthy children as a control group. Estimation of iron status parameters was done. Urinary hepcidin-25 level was detected. Results Urinary hepcidin-25 level was significantly lower in all stages of iron deficiency than in control group, more significant reduction in its level was observed with the progress in severity of iron deficiency. Urinary hepcidin showed significant positive correlation with hemoglobin, mean corpuscular volume, hematocrit value, serum iron and ferritin and transferrin saturation. In contrary, it showed significant negative correlation with serum transferrin and total iron binding capacity. Urinary hepcidin at cutoff point ≤0.94 nmol/mmol Cr could Predict ID stage-1 with sensitivity 88% and specificity 88%. Cutoff point ≤0.42 nmol/mmol Cr could predict ID stage-2 with sensitivity 96% and specificity 92%. Cutoff point ≤0.08 nmol/mmol Cr could Predict ID stage-3 with Sensitivity 96% and specificity 100%. Conclusions We can conclude that detection of urinary hepcidin-25 level was a simple and non invasive test and could predict iron deficiency very early, before appearance of hematological affections.